Performance of Booroola Merino and Finnsheep crossbred lambs and ewes - Young, L. D.; Dickerson, G. E. (Agricultural and Food Science, 1988)
Booroola Merino (B, n= 18) and Finnsheep (F, n =31) rams were mated to F ewes and C3 ewes (1/2 Columbia, 1/4 Suffolk, 1/4 Hampshire). Progeny of these matings were evaluated for performance traits including ewe reproduction through 3 years of age. Averaged over dam breeds, there was no significant difference between B and F sires for conception rate (CR), litter size (LS) at birth or weaning or for lamb mortality to weaning. The difference among sire breeds was not large or significant for birth weight but F sired lambs were significantly heavier than B sired lambs at 63 and 147 days of age. Relative to F sired lambs, B sired lambs had a higher dressing percentage and less fat at the 12th rib but equal estimated percentage kidney fat. A significantly smaller percentage of B-C3 than F, F-C3 or B-F ewe lambs reached puberty by the end of their first breeding season. Ovulation rate at first mating was higher but embryo survival rate tended to be lower for B sired ewes than for F sired ewes. At 2 years of age, B sired ewes produced about 1 kg more wool than F sired ewes. With the exception of the very poor CR of B-C3 ewes at first parity, the differences between the four ewe genotypes were not large or significant for CR at first, second and third parity. The difference between B and F sired ewes in LS at birth was not significant at first parity but B sired ewes were more prolific at second and third parities. However, differences in lamb mortality reduced, and in some cases removed, the differences in LS by weaning time. Relative use of these breeds in commercial U.S. production schemes is discussed.